2018
DOI: 10.1159/000495520
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chronic Coenzyme Q10 Supplementation on Cognitive Function, Learning, and Memory in Healthy and Diabetic Middle-Aged Rats

Abstract: Diabetes mellitus can induce impairment in learning and memory. Cognitive and memory deficits are common in older adults and especially in those with diabetes. This is mainly because of hyperglycemia, oxidative stress, and vascular abnormalities. Coenzyme Q10 (CoQ10) can decrease oxidative stress, hyperglycemia, and inflammatory markers, and improve vascular function. Therefore, the aim of the present study was to investigate the possible effects of CoQ10 on cognitive function, learning, and memory in middle-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 77 publications
(74 reference statements)
1
11
0
Order By: Relevance
“…The obtained findings of this research study confirm that diosgenin administration to STZ-diabetic rats could improve learning and memory disturbances through appropriate modulation of NF-κB/TLR4/Nrf2 and attenuation of astrogliosis biomarker, restoration of cholinergic function, and mitigation of oxidative and inflammatory responses in addition to its neuroprotective potential. DM-associated cognitive deficits have already been reported, as shown by the poor performance of diabetic animals in the passive avoidance test, Y-maze [39], radial arm maze [40, 41], and novel object discrimination tasks [42] which is also consistent with our obtained behavioral data.…”
Section: Discussionsupporting
confidence: 92%
“…The obtained findings of this research study confirm that diosgenin administration to STZ-diabetic rats could improve learning and memory disturbances through appropriate modulation of NF-κB/TLR4/Nrf2 and attenuation of astrogliosis biomarker, restoration of cholinergic function, and mitigation of oxidative and inflammatory responses in addition to its neuroprotective potential. DM-associated cognitive deficits have already been reported, as shown by the poor performance of diabetic animals in the passive avoidance test, Y-maze [39], radial arm maze [40, 41], and novel object discrimination tasks [42] which is also consistent with our obtained behavioral data.…”
Section: Discussionsupporting
confidence: 92%
“…Coenzyme Q10 supplementation was effective in decreasing oxidative stress and related symptoms in autistic children [88]. CoQ10 supplementation has been reported to have enhancement effect on learning and memory in human and animal studies [89]. Abdelraouf et al [90] suggested that children with learning disabilities exhibit memory and linguistic deficits that could be linked to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…This study indicated that CoQ 10 supplementation slightly but significantly reduced fasting blood glucose, although it does not support the existence of significant effects on fasting insulin and glycosylated hemoglobin [189]. Moreover, results from animal studies suggest that dietary CoQ 10 would prevent or mitigate diabetes complications [197,198]. In relation to other metabolic alterations, supplementation with CoQ 10 has also shown beneficial effects on the treatment of hypercholesterolemia and hypertriglyceridemia by modifying blood lipid concentration.…”
Section: Dietary Supplementation Of Coq10 During Agingmentioning
confidence: 99%